La dictionnairique Internet : l’exemple du dictionnaire des synonymes du CRISCO - Jean-Luc Manguin (Corela)
Generally, we can understand dictionarics as the building of the « container », while the « contained » is a matter of lexicography. Through our experience of an on-line dictionary of synonyms, we show that this type of dictionary, which has recently appeared, is interesting both for its user and for its author and designer. An on-line resource is interesting for its users indeed because they benefit from the continuous evolution of the product ; for the authors of dictionaries, the information feedback which is given by the log files of the website can direct this evolution. It is quite easy, indeed, to analyse the requests set out by the users, and then to find the shortages of the database. In addition to their interest coming from their availability, on-line resources may become a powerful learning tool ; for instance, it is possible, from our dictionary of synonyms, to build interactive visualizations of meaning which form a choice aid for the teaching of vocabulary.